ACL injury prevention in daily sports practice - It`s not just the program: Let`s build together, involve the context, and improve the content. - Benjaminse, A.; Verhagen, E. (Sports Medicine, 2021)
Although the benefits of current anterior cruciate ligament (ACL) injury prevention programmes have been demonstrated in efficacy studies, they, unfortunately, have had limited public health impact to date. For example, the incidence of ACL injuries continues to rise in adolescent athletes. Raising awareness and educating coaches and athletes is not enough to facilitate the widespread, sustained use of these programmes in the real-world setting. Considering the profound burden of ACL injuries, it is necessary to continue to improve the current ACL injury prevention programmes through co-creation. First, the uptake of the programmes should be optimized by a better appreciation and understanding of the individual, socio-cultural and environmental context (i.e., community). Second, the content of the programmes should be optimized to better reflect the demands of the sport by creating more ownership and increasing motivation (incorporating challenging, sport-specific and fun elements) with the end-users. In addition, implicit motor learning, random practice and differential learning are concepts that should be integrated when practising to obtain the most optimal results when learning or finetuning skills.